Generalized dual Pell quaternions - Aydin, Fugen Torunbalci; Koklu, Kevser; Yuce, Salim (BULGARIAN ACAD SCIENCE, 2017)
In this paper, we defined the generalized dual Pell quaternions. Also, we investigated the relations between the generalized dual Pell quaternions. Furthermore, we gave the Binet's formulas and Cassini-like identities for these quaternions.
Keywords: Pell number; Pell quaternion; Lucas quaternion; Dual quaternion; COMPLEX FIBONACCI NUMBERS; Mathematics